A cross-country comparison of secondhand smoke exposure among adults: findings from the Global Adult Tobacco Survey (GATS). Issue 4 (27th September 2012) - King, Brian A; Mirza, Sara A; Babb, Stephen D; ,
Abstract : Objective: Exposure to secondhand smoke (SHS) from burning tobacco products causes disease and premature death among non-smoking adults and children. The objective of this study was to determine the nature, extent and demographic correlates of SHS exposure among adults in low- and middle-income countries with a high burden of tobacco use. Methods: Data were obtained from the Global Adult Tobacco Survey (GATS), a nationally representative household survey of individuals 15 years of age or older. Interviews were conducted during 2008–2010 in Bangladesh, Brazil, China, Egypt, India, Mexico, the Philippines, Poland, Russia, Thailand, Turkey, Ukraine, Uruguay and Vietnam. Descriptive statistics were used to determine the prevalence and correlates of SHS exposure in homes, workplaces, government buildings, restaurants, public transportation and healthcare facilities. Results: Exposure to SHS in the home ranged from 17.3% (Mexico) to 73.1% (Vietnam). Among those who work in an indoor area outside the home, SHS exposure in the workplace ranged from 16.5% (Uruguay) to 63.3% (China). Exposure to SHS ranged from 6.9% (Uruguay) to 72.7% (Egypt) in government buildings, 4.4% (Uruguay) to 88.5% (China) in restaurants, 5.4% (Uruguay) to 79.6% (Egypt) on public transportation, and 3.8% (Uruguay) to 49.2% (Egypt) in healthcare facilities. Conclusions: A large proportion of adults living in low- and middle-income countries are exposed to SHS in their homes, workplaces, and other public places. Countries can enact and enforce legislation requiring 100% smoke-free public places and workplaces, and can also conduct educational initiatives to reduce SHS exposure in homes.